PEMETAAN STRATEGI PEMASARAN PERPUSTAKAAN DI GOOGLE SCHOLAR MELALUI PUBLISH OF PERISH - Retno Ambarini; Yesti Hawa (Jurnal Riset Rumpun Ilmu Bahasa, 2023)
A large body of research on library marketing, published in open access journals and included in open access databases such as Google Scholar, needs to be evaluated. Bibliographic analysis becomes a parameter for evaluating research results to determine the relationship between science and technology, map a particular scientific field, and monitor the development of new knowledge in a particular scientific field. The purpose of this study is to map the evolution of library marketing research indexed in Google Scholar, analyze topics related to library marketing, and identify researchers who have worked on those topics. In this research, a qualitative method based on the theme analysis approach is adopted as a data analysis method. This study uses the Publish or Perish (PoP) application to collect research data obtained from studies indexed by the keyword "library marketing" in Google Scholar. This sample was determined by screening publications in the form of journal articles published between 2018 and 2023. Study data were analyzed using the VOSviewer application. The relationship between library marketing and strategy is illustrated by the keyword mapping results in the article titled "Library Marketing Mix Strategy for the Digital Age." It was also noted that a library marketing study was conducted by 20 researchers from 2019 to 2023.